2007
DOI: 10.1007/s00044-007-9002-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant effects of polysaccharides extracted from Lycium barbarum

Abstract: Lycium barbarum, a famous Chinese medicinal herb, has a long history of use as a traditional remedy for many diseases. Polysaccharides are the most important functional constituent in Lycium barbarum fruits. In the present study, the antioxidant activity of polysaccharides extracted from Lycium barbarum fruits growing in Xin Jiang, a northwest province of China, was evaluated. Six established in vitro methods, including superoxide radical (O 2 -) scavenging activity, reducing power, b-carotene linoleate model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 30 publications
0
30
0
3
Order By: Relevance
“…In case of DPPH radical scavenging activity, the activity was directly proportional to the concentration of the anti-oxidants. The DPPH radical scavenging method was based on the reduction in the methanol DPPH solution in the presence of a hydrogen donating antioxidant, due to the formation of the non-radical form DPPH-H (Li and Zhou, 2007). It was observed that the carotenoids were able to reduce and decolor 1,1-diphenyl-2-picrylhydrazyl, via their hydrogen donating ability both in encapsulated form and before encapsulation.…”
Section: Antioxidative Assaymentioning
confidence: 99%
“…In case of DPPH radical scavenging activity, the activity was directly proportional to the concentration of the anti-oxidants. The DPPH radical scavenging method was based on the reduction in the methanol DPPH solution in the presence of a hydrogen donating antioxidant, due to the formation of the non-radical form DPPH-H (Li and Zhou, 2007). It was observed that the carotenoids were able to reduce and decolor 1,1-diphenyl-2-picrylhydrazyl, via their hydrogen donating ability both in encapsulated form and before encapsulation.…”
Section: Antioxidative Assaymentioning
confidence: 99%
“…We referred to the methods in the literature (Zheng et al, 2010;Li et al, 2006b) and made minor modifications. Precisely, DPPH powder was weighed, dissolved with methanol, and prepared into 6mmol/L solution for later use.…”
Section: Dpph Free Radical Clearance Testmentioning
confidence: 99%
“…Pharmacological investigations on the antioxidant effect of L. barbarum mainly attributed this capacity to L. barbarum polysaccharides (LBP) (Li et al, 2007a;Li & Zhou, 2007), but also to other components such as flavonoids or carotenoids (Le et al, 2007;Jiang, 2014). The mechanism of action of both classes of compounds includes metal reducing and chelating capabilities, as well as the ability to clean free radicals (Li & Zhou, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of both classes of compounds includes metal reducing and chelating capabilities, as well as the ability to clean free radicals (Li & Zhou, 2007).…”
Section: Discussionmentioning
confidence: 99%